Modified thermoplastic polyurethane elastomer foamed bead as well as preparation method and application thereof
By mixing the TPU with LCPAE and processing aids, and processing it with water and supercritical fluid in the autoclave, the pressure relief foaming process is used to prepare modified TPU foaming beads, which solves the shrinkage problem of TPU foaming materials during the foaming process, and achieves high-efficiency, low-density, and high-resilience foaming material preparation.
Patent Information
- Application Number
- CN202411558881.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-18
AI Technical Summary
TPU foaming materials have shrinkage problems during foaming, resulting in poor appearance, collapse of cell walls, increased density and long production cycle.
Modified TPU foamed beads were prepared by uniformly mixing the thermoplastic polyurethane elastomer (TPU) with long carbon chain polyamide thermoplastic elastomer (LCPAE) and processing aids, and treated with water and supercritical fluid in an autoclave.
The efficiency of foaming processing is significantly improved, the shrinkage rate of foamed beads is reduced, and the foamed material with a round appearance, low density, and high rebound are obtained, and the maturation cycle is shortened and production costs are reduced.
Smart Images

Figure CN119639070A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foaming of polymer materials, and in particular relates to modified thermoplastic polyurethane elastomer foaming beads and a preparation method and application thereof. Background Art
[0002] The supercritical physical foaming process usually uses inert gases such as carbon dioxide and nitrogen as foaming agents. These inert gases can reach a supercritical state under high temperature and high pressure conditions and are used for physical foaming to prepare low-density porous materials. This preparation method does not emit toxic chemicals during the preparation process, does not require chemical cross-linking, makes the entire foaming process pollution-free, and the resulting foamed material can be recycled. Therefore, this preparation method has received widespread attention and application in the preparation of thermoplastic elastomer foaming materials. Through the supercritical foaming process, thermoplastic elastomers can be first prepared into microparticles through underwater granulation for bead foaming; they can also be directly injection molded for overall foaming; or the foaming material can be prepared by first immersing in a supercritical medium and then simultaneously foaming and molding in the mold.
[0003] Thermoplastic polyurethane elastomer (TPU) has the advantages of excellent mechanical strength, low-temperature elasticity, hydrolysis resistance, aging resistance and recyclability. The TPU bead foaming and molding technology jointly developed by BASF of Germany and Adidas has successfully produced lightweight and highly elastic shoe materials, leading the development of the industry. The technology first uses a supercritical foaming process to make TPU pellets into foam beads, and then uses steam compression molding to prepare foamed parts.
[0004] However, the hard segment content of TPU materials is low, the crystallinity and crystallization temperature are low, and the formed crystal structure is imperfect. In the process of pressure drop foaming using supercritical medium, the cooling crystallization of the sample and the growth of the pores are carried out simultaneously. Due to the rapid foaming expansion speed, it is difficult to form an ideal crystal structure; in addition, the supercritical foaming medium is partially released into the atmosphere when exchanging with air, resulting in shrinkage and collapse of the pore wall of the TPU foaming beads.
[0005] In order to solve the problem of further shrinkage of TPU foam beads, a long aging treatment is usually required, such as placing the foam beads in an oven for annealing to improve the crystallinity and modulus of the sample and inhibit shrinkage and collapse. However, this method reduces production efficiency and increases costs, and the effect is not ideal.
[0006] Chinese patent CN104130439 discloses a technology for preparing TPU foamed particles by two-step decompression foaming using supercritical carbon dioxide as a medium. This method requires the TPU material to be boiled in water, which not only causes material degradation, but also limits the types of TPU that can be used.
[0007] Chinese patent CN103951965 discloses a technology for preparing colored TPU foaming materials, which uses supercritical carbon dioxide as a medium, performs one-step foaming through a water bath or steam, then performs secondary foaming through hot air, and finally performs tertiary foaming through high-pressure air or nitrogen to prepare the foaming material. It can be seen that the process flow and equipment of this method are complex and the cost is high. The TPU beads after foaming have serious shrinkage problems, with a size shrinkage rate of more than 50%. This severe shrinkage not only significantly increases the density of the foaming material, but also causes obvious wrinkles and depressions on the surface of the foaming material, and the appearance is shriveled, which restricts its subsequent use.
[0008] Chinese patent CN103642200 discloses a technology for adjusting the cell size of TPU foam beads and reducing shrinkage by introducing cell size stabilizers and melt viscosity modifiers. The patented method boils TPU particles in water at a temperature of 100-150°C, but polyester TPU resin is easy to hydrolyze, and long-term boiling in water can easily lead to its degradation and yellowing, so the actual effect is still not ideal.
[0009] Therefore, how to solve the problems of poor appearance, cell wall collapse, increased density and long production cycle caused by shrinkage of TPU foam materials is a difficult problem that needs to be solved urgently in this field.
[0010] In view of this, the present invention is proposed. Summary of the invention
[0011] The purpose of the present invention is to provide a modified thermoplastic polyurethane elastomer foaming bead and a preparation method and application thereof. The modified TPU foaming beads prepared by the present invention have a high setting rate and a low shrinkage rate, which significantly improves the efficiency of the foaming process and obtains a foaming material with a rounded appearance, low density and high resilience.
[0012] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0013] A method for preparing modified thermoplastic polyurethane elastomer foam beads comprises the following steps:
[0014] (1) mixing a thermoplastic polyurethane elastomer, a long carbon chain polyamide thermoplastic elastomer and a processing aid uniformly and then extruding and granulating the mixture to obtain modified thermoplastic polyurethane elastomer foamed particles;
[0015] (2) placing the modified thermoplastic polyurethane elastomer foamed particles and water into a high-pressure reactor and stirring them, then filling the high-pressure reactor with a supercritical fluid to reach a preset pressure, and simultaneously heating the high-pressure reactor to a softening temperature of the modified thermoplastic polyurethane elastomer and maintaining the temperature for a predetermined time to allow the modified thermoplastic polyurethane elastomer to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system;
[0016] (3) The polymer-supercritical fluid homogeneous system is depressurized and foamed to obtain modified thermoplastic polyurethane elastomer foam beads.
[0017] Thermoplastic polyurethane elastomer (TPU) is a linear block copolymer composed of two different types of segments, "hard segment" and "soft segment". The hard segment is generated by the reaction of isocyanate and chain extender (usually small molecule diol or diamine), and the isocyanate includes aromatic or aliphatic types; the soft segment is usually composed of high molecular weight polyols, including polyester polyols or polyether polyols.
[0018] The performance of TPU can be effectively improved by uniformly mixing thermoplastic polyurethane elastomer (TPU) with long carbon chain polyamide thermoplastic elastomer (LCPAE) and processing aids and extruding them into granules. The addition of LCPAE provides a modification method for TPU, especially in the preparation process of foaming beads. The high crystallization temperature and rapid crystallization characteristics of LCPAE can provide better structural support when the pores are formed, inhibiting the collapse and shrinkage of the pores.
[0019] The modified foamed particles and water are placed in a high-pressure reactor and filled with supercritical fluid for saturation treatment. Due to the high crystallization rate and good nucleation effect of LCPAE, the saturated state of the modified foamed particles in the supercritical fluid can distribute the gas more evenly and form a good bubble structure. Compared with pure TPU, the introduction of LCPAE allows the material to form a more stable pore structure during the pore growth process, reducing the rupture and collapse of the pore wall during the foaming process, thereby improving the foaming efficiency and reducing the shrinkage rate of the foamed beads.
[0020] Through the pressure relief foaming process, the supercritical fluid expands rapidly in the material to form bubbles. The high modulus hard segment provided by LCPAE can resist the shrinkage stress during the foaming process and ensure the dimensional stability of the bubbles. At the same time, in the mixed system of TPU and LCPAE, the hydrogen bond network formed by the hard segment of LCPAE helps to improve the mechanical strength and resilience of the foamed beads, significantly improving the mechanical properties of the foamed material. This makes the final foamed beads have good resilience, shock absorption and dimensional stability, which is very suitable for use in high-end shoe materials, shock-absorbing packaging and other fields.
[0021] The rapid crystallization of LCPAE can accelerate the shaping rate of foamed beads, reduce the shrinkage of beads after foaming, and thus shorten the aging cycle. Compared with traditional TPU foamed beads, which require a long annealing process to improve crystallinity and stability, the modified system of the present invention can effectively reduce the aging process time, reduce production energy consumption and costs, and improve production efficiency.
[0022] Furthermore, the thermoplastic polyurethane elastomer is 100 parts by weight, and the long carbon chain polyamide thermoplastic elastomer is 20 to 50 parts by weight;
[0023] Preferably, the processing aid is selected from one or more of a chain extender, an antioxidant, a nucleating agent or a lubricant;
[0024] Preferably, the processing aid includes 0.01-2 parts by weight of a chain extender, 0.01-5 parts by weight of an antioxidant, and 0.01-5 parts by weight of a nucleating agent.
[0025] Furthermore, the thermoplastic polyurethane elastomer is polyether polyurethane and / or polyester polyurethane;
[0026] Preferably, the isocyanate of the thermoplastic polyurethane elastomer is selected from one or more of aliphatic isocyanate, alicyclic isocyanate and aromatic isocyanate;
[0027] Preferably, the isocyanate of the thermoplastic polyurethane elastomer is selected from one or more of aromatic polyisocyanates and aliphatic polyisocyanates;
[0028] Preferably, the hardness of the thermoplastic polyurethane elastomer is 30-40D on Shore A;
[0029] Preferably, the isocyanate of the thermoplastic polyurethane elastomer is selected from one or more of 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 2,2'-diphenylmethane diisocyanate (2,2'-MDI), xylylene diisocyanate (XDI), 1,5-naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), 1,4-cyclohexyl diisocyanate (CHDI), hexamethylene diisocyanate (HDI), decane-1,10-diisocyanate and dicyclohexylmethane-4,4'-diisocyanate (H12MDI);
[0030] Preferably, the isocyanate of the thermoplastic polyurethane elastomer is 4,4'-diphenylmethane diisocyanate (4,4'-MDI).
[0031] Further, the polyol of the thermoplastic polyurethane elastomer is selected from one or more of polyester polyol, polylactone polyol, polycarbonate polyol and polyether polyol;
[0032] Preferably, the polyol of the thermoplastic polyurethane elastomer is a polyether polyol.
[0033] Further, the chain extender of the thermoplastic polyurethane elastomer is selected from one or more diols having 2 to 10 carbon atoms;
[0034] Preferably, the chain extender of the thermoplastic polyurethane elastomer is selected from one or more of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,3-butanediol, 1,5-pentanediol, 1,4-cyclohexanediol, hydroquinone di(hydroxyethyl) ether and neopentyl glycol;
[0035] Preferably, the chain extender of the thermoplastic polyurethane elastomer is 1,4-butanediol.
[0036] Furthermore, the long carbon chain polyamide thermoplastic elastomer is formed by polycondensation of a polyamide hard segment and a polyether soft segment, wherein the carbon number of the diamine and the carbon number of the dibasic acid are 2N2(N+1);
[0037] Since only partial hydrogen bonds can be formed between adjacent molecular chains of odd-odd, even-odd and odd-even polyamides, the hydrogen bond interactions of elastomers produced with these types of polyamide hard segments are weak, and they have lower crystallization temperatures and slower crystallization rates. The foamed beads prepared in this way have greater shrinkage and are prone to problems such as poor appearance, collapse of pore walls, increased density and long production cycles. Among even-even polyamides, the inventors have found through research that the stable crystal form of the 2N2(N+1) type polyamide crystal structure is α-type. The LCPAE with this crystal form has a large modulus and can resist the shrinkage stress caused by high expansion ratio. When 2N2(N+1) type polyamide is used as a hard segment and copolymerized with a polyether soft segment by a bulk melt method to prepare a low-hardness LCPAE elastomer, the number of methylene groups in the dibasic acid fatty chain and the diamine fatty chain of this type of polyamide is equal, and a highly symmetrical hard segment structure can be formed. This spatial arrangement allows strong hydrogen bond interactions to form between the amide bonds. Therefore, the long carbon chain polyamide elastomer prepared from this type of polyamide hard segment has a higher crystallization temperature and a faster crystallization rate even if the hard segment content is not high and the apparent hardness is not large. The shrinkage rate of the foamed beads prepared from this type of elastomer is lower.
[0038] Preferably, the polyamide hard segment and the polyether soft segment are connected by an ester bond or an amide bond;
[0039] Preferably, the polyamide hard segment is selected from one or more of polyamide 1416, polyamide 1214, polyamide 1012 or polyamide 810;
[0040] Preferably, the polyamide hard segment is selected from polyamide 1214 and polyamide 1012;
[0041] Preferably, the polyamide hard segment is polyamide 1012;
[0042] Preferably, the polyether soft segment is selected from one or more of polyoxyethylene ether, polyoxypropylene ether, and polytetramethylene oxide ether;
[0043] Preferably, the polyether soft segment is polytetramethylene oxide.
[0044] Furthermore, in step (2), the supercritical fluid includes supercritical CO2 and / or supercritical N2, the preset pressure is 10-25 MPa, the softening temperature of the long carbon chain polyamide elastomer foamed particles is 90-160°C, and the preset time is 30-120 min;
[0045] Preferably, the preset pressure is 12-15 MPa, the softening temperature of the modified thermoplastic polyurethane elastomer foamed particles is 110-130° C., and the predetermined time is 60-90 min.
[0046] Furthermore, in the step (3), a rapid pressure relief method is used for pressure relief, and the pressure relief rate is 10-60 MPa / min;
[0047] Preferably, the pressure relief rate is 30-40 MPa / min.
[0048] The present invention also provides a modified thermoplastic polyurethane elastomer foaming bead, which is prepared by any preparation method described in the above technical scheme and has a density of 0.1-0.3 g / cm 3 The cell diameter of the foamed beads is 10-100 μm, and the cell density is 2×10 7 -2×10 9 Pieces / cm 3 .
[0049] The present invention also provides an application of the modified thermoplastic polyurethane elastomer foaming beads as described in any of the above technical solutions in the preparation of foaming materials, wherein the modified thermoplastic polyurethane elastomer foaming beads are placed in a mold cavity of a molding machine, steam is introduced and heated at a pressure of 0.1-0.4 MPa until the foaming beads expand, extrude and adhere to each other, and after cooling and demolding, a density of 0.15-0.35 g / cm is formed. 3 Foaming material;
[0050] Preferably, the heating temperature is 100-150°C and the heating time is 10-120s;
[0051] Preferably, the pressure of the water vapor introduced is 0.2-0.3 MPa, the heating temperature is 110-130° C., and the heating time is 20-40 s.
[0052] After adopting the above technical scheme, the present invention has the following beneficial effects compared with the prior art.
[0053] The invention mixes thermoplastic polyurethane elastomer (TPU) with long carbon chain polyamide thermoplastic elastomer (LCPAE) and processing aid and extrude and granulate, which can effectively improve the performance of TPU. The addition of LCPAE provides a modification method for TPU, especially in the preparation process of foaming beads, the high crystallization temperature and rapid crystallization characteristics of LCPAE can provide better structural support when the pores are formed, and inhibit the collapse and shrinkage of the pores.
[0054] The modified foamed particles and water are placed in a high-pressure reactor and filled with supercritical fluid for saturation treatment. Due to the high crystallization rate and good nucleation effect of LCPAE, the saturated state of the modified foamed particles in the supercritical fluid can distribute the gas more evenly and form a good bubble structure. Compared with pure TPU, the introduction of LCPAE allows the material to form a more stable pore structure during the pore generation process, reducing the rupture and collapse of the pore wall during the foaming process, thereby improving the foaming efficiency and reducing the shrinkage rate of the foamed beads.
[0055] Through the pressure relief foaming process, the supercritical fluid expands rapidly in the material to form bubbles. The high modulus hard segment provided by LCPAE can resist the shrinkage stress during the foaming process and ensure the dimensional stability of the bubbles. At the same time, in the mixed system of TPU and LCPAE, the hydrogen bond network formed by the hard segment of LCPAE helps to improve the mechanical strength and resilience of the foamed beads, significantly improving the mechanical properties of the foamed material. This makes the final foamed beads have good resilience, shock absorption and dimensional stability, which is very suitable for use in high-end shoe materials, shock-absorbing packaging and other fields.
[0056] The rapid crystallization of LCPAE can accelerate the shaping rate of foamed beads, reduce the shrinkage of beads after foaming, and thus shorten the aging cycle. Compared with traditional TPU foamed beads, which require a long annealing process to improve crystallinity and stability, the modified system of the present invention can effectively reduce the aging process time, reduce production energy consumption and costs, and improve production efficiency.
[0057] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:
[0059] In the figure:
[0060] Figure 1, is a cross-sectional scanning electron microscope image of the modified TPU foamed beads of Example 1 of the present invention;
[0061] Figure 2 , a foaming material sheet prepared by steam molding the modified TPU foaming beads of Example 1 of the present invention;
[0062] Figure 3 , is a cross-sectional scanning electron microscope image of the modified TPU foamed beads of Example 2 of the present invention;
[0063] Figure 4 , is a cross-sectional scanning electron microscope image of the foamed beads of comparative example 1 of the present invention.
[0064] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0065] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0066] Example 1
[0067] Preparation of modified thermoplastic polyurethane elastomer foam beads:
[0068] (1) Preparation of PA1012-based LCPAE:
[0069] 207 kg of dodecyl dibasic acid and 102 kg of decanediamine were added to a 1500 L high-pressure reactor, and the air in the reactor was replaced with a nitrogen flow for 10 minutes. The reactor was heated to 250°C under a nitrogen flow atmosphere, and the nitrogen flow was turned off after 1 hour. The reactor was kept in a closed state, and the mixed materials continued to react in the reactor for 1 hour;
[0070] Then, the pressure in the reactor was reduced to -98 kPa by vacuum pumping, and the vacuum was maintained for 30 min after dehydration, and then the vacuum was stopped. Then, nitrogen was used to restore the pressure to a state slightly greater than the atmospheric pressure, and then 300.0 kg of PTMEG2000, 0.05 kg of catalyst tetrabutoxytitanium, and 1 kg of 1098 antioxidant were added to the reactor;
[0071] The mixture was heated to 250°C and stirred for 30 minutes under a nitrogen atmosphere, and then evacuated to -98 kPa. After reacting at a constant pressure for 3 hours, the material was discharged from the bottom of the kettle, and then pelletized through underwater drawing to obtain PA1012-based long-chain polyamide elastomer A (LCPAE-A); the characteristic viscosity of PA1012-based long-chain polyamide elastomer A was 0.16 dL / g, the tensile strength of the injection-molded specimen was 21.2 MPa, the elongation at break was 860%, and the Shore hardness was 41D.
[0072] (2) 70 kg of TPU Ellaston 1185A with a Shore hardness of 40D purchased from BASF, 30 kg of dry LCPAE-A with a hardness of 40D, 0.5 kg of 1098 antioxidant, 0.1 kg of HPN-20E nucleating agent, 0.5 kg of KL-E4370 multifunctional epoxy chain extender, and 0.5 kg of silica were mixed uniformly by a high-speed mixer, and the mixed materials were put into an extruder for melt blending, and ellipsoidal modified thermoplastic polyurethane elastomer foamed particles (UA1) were obtained by underwater pelletizing;
[0073] (3) 1 kg of the modified thermoplastic polyurethane elastomer foamed particles (UA1) and 2 kg of water were added to a 30 L high-pressure foaming reactor, and stirring was started at a speed of 10 r / min. High-pressure CO2 was then injected through a plunger pump while heating was performed. When the temperature in the reactor reached 125° C. and the pressure reached 15 MPa, pressurization and heating were stopped, and the temperature and pressure were maintained for 60 min to allow the particles to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system;
[0074] (4) opening the discharge valve at the bottom of the autoclave, and releasing the pressure on the polymer-supercritical fluid homogeneous system at a rate of 30 MPa / min to foam the modified thermoplastic polyurethane elastomer foam beads (UA1-F1); the apparent density of the modified thermoplastic polyurethane elastomer foam beads (UA1-F1) is 0.15 g / cm 3 ; The internal pore morphology of the obtained foamed beads was analyzed by SEM (such as Figure 1 shown);
[0075] Take 5 UA1-F1 foam beads and place them in a laboratory at 25°C and 50% humidity for 48 hours. Observe the appearance of the LCPAE foam beads (UA1) and test the apparent density once every 24 hours to determine the shrinkage of the UA1-F1 foam beads (as shown in Table 1). As shown in Table 1, the shrinkage rate of the UA1-F1 foam beads after 24 hours is 13.3%, and the shrinkage rate after 48 hours is still 13.3%.
[0076] (5) In a steam forming machine, the water vapor pressure is set to 0.22 MPa, the temperature is set to 113° C., and the heating time is set to 30 s. The modified thermoplastic polyurethane elastomer foam beads (UA1-F1) can be used to prepare a sheet ( Figure 2 As shown), the sheet density is 0.16g / cm 3 , vertical rebound reaches 68%, tensile strength is 1.6MPa, and elongation at break is 246% (as shown in Table 2).
[0077] Example 2
[0078] 1 kg of the modified thermoplastic polyurethane elastomer foamed particles (UA1) in Example 1 and 2 kg of water were added to a 30 L high pressure foaming kettle, and stirred at a speed of 10 r / min, and then high pressure CO2 was injected through a plunger pump, and heating was performed at the same time. When the temperature in the kettle reached 125°C and the pressure reached 10 MPa, pressurization and heating were stopped. The temperature and pressure were maintained for 60 minutes to allow the foaming to reach a saturated state, and a polymer-supercritical fluid homogeneous system was obtained.
[0079] The discharge valve at the bottom of the autoclave was opened, and the polymer-supercritical fluid homogeneous system was depressurized and foamed at a rate of 30 MPa / min to obtain modified thermoplastic polyurethane elastomer foam beads (UA1-F2); the apparent density of the modified thermoplastic polyurethane elastomer foam beads (UA1-F2) was 0.2 g / cm 3 ; The internal pore morphology of the obtained foamed beads was analyzed by SEM.
[0080] Take 5 UA1-F2 foam beads and place them in a laboratory at 25°C and 50% humidity for 72 hours. Observe the appearance of the LCPAE foam beads (UA1) and test the apparent density once every 24 hours to determine the shrinkage of the UA1-F2 foam beads (as shown in Table 1). As can be seen from Table 1, the shrinkage rate of the UA1-F2 foam beads after 24 hours is 10%, and the shrinkage rate after 48 hours is 13.6%.
[0081] In the steam forming machine, the water vapor pressure was set to 0.22 MPa, the temperature was set to 113 °C, and the heating time was set to 30 s. The modified thermoplastic polyurethane elastomer foam beads (UA1-F2) were used to prepare a sheet with a density of 0.23 g / cm 3 , vertical rebound reaches 65%, tensile strength is 1.9MPa, and elongation at break is 274% (as shown in Table 2).
[0082] Example 3
[0083] (1) Preparation of PA1214-based LCPAE:
[0084] Add 232.0 kg of tetradecyl diacid and 120.0 kg of dodecyl diamine into a 1500 L high-pressure reactor, replace the air in the reactor with a nitrogen flow for 10 minutes, heat to 250° C. in a nitrogen flow atmosphere, and turn off the nitrogen flow after 1 hour, keep the reactor in a closed state, and continue to react the mixture in the reactor for 2 hours;
[0085] Then, the pressure in the reactor was reduced to -98 kPa by vacuum pumping, and the vacuum was maintained for 30 minutes after dehydration, and then the vacuum was stopped. Then, nitrogen was used to restore the pressure to a state slightly greater than the atmospheric pressure, and then 600 kg of PTMEG 3000, 0.05 kg of catalyst tetrabutoxytitanium, and 1 kg of 1098 antioxidant were added to the reactor.
[0086] The mixture was heated to 255°C and stirred for 30 minutes under a nitrogen atmosphere, and then vacuumed to -98 kPa. After reacting at a constant pressure for 3 hours, the mixture was discharged from the bottom of the kettle, and then pelletized by underwater drawing to obtain PA1214-based LCPAE-B. The intrinsic viscosity of PA1214-based LCPAE-B is 0.15 dL / g, the tensile strength of the injection molded strip is 17.5 MPa, the elongation at break is 980%, and the Shore hardness is 41D.
[0087] (2) 70 kg of TPU Ellaston 1185A with a Shore hardness of 40D purchased from BASF, 30 kg of dry LCPAE-B with a hardness of 41D, 0.5 kg of 1098 antioxidant, 0.1 kg of HPN-20E nucleating agent, 0.5 kg of KL-E4370 multifunctional epoxy chain extender, and 0.5 kg of silica were mixed uniformly by a high-speed mixer, and the mixed materials were put into an extruder for melt blending, and ellipsoidal modified thermoplastic polyurethane elastomer foamed particles (UA2) were obtained by underwater pelletization;
[0088] (3) 1 kg of the modified thermoplastic polyurethane elastomer foamed particles (UA2) and 2 kg of water are added to a 30 L high-pressure foaming reactor, and stirring is started at a speed of 10 r / min. Then, high-pressure CO2 is injected through a plunger pump and heating is performed at the same time. When the temperature in the reactor reaches 115°C and the pressure reaches 15 MPa, pressurization and heating are stopped, and the temperature and pressure are maintained for 60 minutes to allow the long-chain polyamide elastomer foamed particles to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system.
[0089] (4) Opening the discharge valve at the bottom of the autoclave, releasing the pressure on the polymer-supercritical fluid homogeneous system at a rate of 30 MPa / min to foam the modified thermoplastic polyurethane elastomer foam beads (UA2-F1); the apparent density of the modified thermoplastic polyurethane elastomer foam beads (UA2-F1) is 0.16 g / cm 3 ; The internal pore morphology of the obtained foamed beads was analyzed by SEM (such as Figure 3 shown);
[0090] Take 5 foam beads and place them in a laboratory at 25°C and 50% humidity for 72 hours. Observe the appearance and test the apparent density every 24 hours to determine the shrinkage of the foam beads (as shown in Table 1). As shown in Table 1, the shrinkage rate after 24 hours is 12.5%, and the shrinkage rate after 48 hours is 18.8%.
[0091] In the steam forming machine, the water vapor pressure is set to 0.22 MPa, the temperature is 113 ° C, and the heating time is 30 s. The UA2-F1 foamed beads can be used to prepare a sheet with a density of 0.21 g / cm 3 , vertical rebound reaches 67%, tensile strength is 1.8MPa, and elongation at break is 232% (as shown in Table 2).
[0092] Example 4
[0093] 1 kg of the modified thermoplastic polyurethane elastomer foamed particles (UA2) in Example 3 and 2 kg of water are added to a 30 L high-pressure foaming kettle, and stirring is started at a speed of 10 r / min. Then, high-pressure CO2 is injected through a plunger pump and heating is performed at the same time. When the temperature in the kettle reaches 115°C and the pressure reaches 10 MPa, pressurization and heating are stopped, and the temperature and pressure are maintained for 60 minutes to allow the foaming to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system.
[0094] The discharge valve at the bottom of the autoclave was opened, and the polymer-supercritical fluid homogeneous system was depressurized and foamed at a rate of 30 MPa / min to obtain modified thermoplastic polyurethane elastomer foam beads (UA2-F2).
[0095] The apparent density of modified thermoplastic polyurethane elastomer foam beads (UA2-F2) is 0.21 g / cm 3 The internal pore morphology of the obtained foamed beads was analyzed by SEM.
[0096] Take 5 UA2-F2 foam beads and place them in a laboratory at 25°C and 50% humidity for 72 hours. Observe the appearance of the LCPAE foam beads (UA2) and test the apparent density once every 24 hours to determine the shrinkage of the UA2-F2 foam beads (as shown in Table 1). As shown in Table 1, the shrinkage rate of the UA2-F2 foam beads after 24 hours is 9.5%, and the shrinkage rate after 48 hours is 14.3%.
[0097] In the steam forming machine, the water vapor pressure was set to 0.22 MPa, the temperature was set to 113 °C, and the heating time was set to 30 s. The modified thermoplastic polyurethane elastomer foam beads (UA2-F2) were used to prepare a sheet with a density of 0.30 g / cm3 , vertical rebound reaches 60%, tensile strength is 2.3MPa, and elongation at break is 301% (as shown in Table 2).
[0098] Example 5
[0099] (1) 83 kg of TPU with a Shore hardness of 30D, 16.6 kg of Pebax 4533 (PA12-based LCPAE) with a Shore hardness of 40D, 0.012 kg of 1098 antioxidant, 0.012 kg of HPN-20E nucleating agent, 0.012 kg of KL-E4370 multifunctional epoxy chain extender, and 0.5 kg of silica were mixed uniformly by a high-speed mixer, and the mixed materials were put into an extruder for melt blending, and ellipsoidal modified thermoplastic polyurethane elastomer foamed particles were obtained by underwater pelletizing;
[0100] (2) adding 1 kg of the modified thermoplastic polyurethane elastomer foamed particles and 2 kg of water into a 30 L high-pressure foaming reactor, stirring at a speed of 10 r / min, and then injecting high-pressure CO2 through a plunger pump while heating. When the temperature in the reactor reaches 90° C. and the pressure reaches 25 MPa, the pressurization and heating are stopped, and the temperature and pressure are maintained for 120 min to allow the particles to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system;
[0101] (3) opening the discharge valve at the bottom of the autoclave, and releasing the pressure of the polymer-supercritical fluid homogeneous system for foaming at a rate of 10 MPa / min to obtain modified thermoplastic polyurethane elastomer foam beads;
[0102] (4) In a steam forming machine, the water vapor pressure was set to 0.1 MPa, the temperature was set to 100° C., and the heating time was set to 120 s, and a sheet was prepared using the modified thermoplastic polyurethane elastomer foam beads.
[0103] Example 6
[0104] (1) Preparation of PA1012-based LCPAE: The preparation method is the same as that in Example 1;
[0105] (2) 67 kg of TPU with a Shore hardness of 35D, 33.5 kg of dry LCPAE-A with a Shore hardness of 40D, 7.46 kg of 1098 antioxidant, 7.46 kg of HPN-20E nucleating agent, 2.99 kg of KL-E4370 multifunctional epoxy chain extender, and 0.5 kg of silica were mixed uniformly by a high-speed mixer, and the mixed materials were put into an extruder for melt blending, and ellipsoidal modified thermoplastic polyurethane elastomer foamed particles were obtained by underwater pelletizing;
[0106] (3) adding 1 kg of the modified thermoplastic polyurethane elastomer foamed particles and 2 kg of water into a 30 L high-pressure foaming reactor, stirring at a speed of 10 r / min, and then injecting high-pressure CO2 through a plunger pump while heating. When the temperature in the reactor reaches 160° C. and the pressure reaches 10 MPa, the pressurization and heating are stopped, and the temperature and pressure are maintained for 30 minutes to allow the particles to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system;
[0107] (4) opening the discharge valve at the bottom of the autoclave, and releasing the pressure of the polymer-supercritical fluid homogeneous system for foaming at a rate of 60 MPa / min to obtain modified thermoplastic polyurethane elastomer foam beads;
[0108] (5) In a steam forming machine, the water vapor pressure was set to 0.4 MPa, the temperature was set to 150° C., and the heating time was set to 10 s, and a sheet was prepared using the modified thermoplastic polyurethane elastomer foam beads.
[0109] Example 7
[0110] (1) Preparation of PA1012-based LCPAE: The preparation method is the same as that in Example 1;
[0111] (2) 71.42 kg of TPU with a Shore hardness of 35D, 28.57 kg of dry LCPAE-A with a Shore hardness of 40D, 0.5 kg of 1098 antioxidant, 0.1 kg of HPN-20E nucleating agent, 0.5 kg of KL-E4370 multifunctional epoxy chain extender, and 0.5 kg of silica were mixed uniformly by a high-speed mixer, and the mixed materials were put into an extruder for melt blending, and ellipsoidal modified thermoplastic polyurethane elastomer foamed particles were obtained by underwater pelletizing;
[0112] (3) adding 1 kg of the modified thermoplastic polyurethane elastomer foamed particles and 2 kg of water into a 30 L high-pressure foaming reactor, stirring at a speed of 10 r / min, and then injecting high-pressure CO2 through a plunger pump while heating. When the temperature in the reactor reaches 110° C. and the pressure reaches 12 MPa, the pressurization and heating are stopped, and the temperature and pressure are maintained for 90 min to allow the particles to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system;
[0113] (4) opening the discharge valve at the bottom of the autoclave, and releasing the pressure of the polymer-supercritical fluid homogeneous system for foaming at a rate of 40 MPa / min to obtain modified thermoplastic polyurethane elastomer foam beads;
[0114] (5) In a steam forming machine, the water vapor pressure was set to 0.2 MPa, the temperature was set to 130° C., and the heating time was set to 20 s, and a sheet was prepared using the modified thermoplastic polyurethane elastomer foam beads.
[0115] Example 8
[0116] (1) Preparation of PA1012-based LCPAE: The preparation method is the same as that in Example 1;
[0117] (2) 71.42 kg of TPU with a Shore hardness of 35D, 28.57 kg of dry LCPAE-A with a Shore hardness of 40D, 0.5 kg of 1098 antioxidant, 0.1 kg of HPN-20E nucleating agent, 0.5 kg of KL-E4370 multifunctional epoxy chain extender, and 0.5 kg of silica were mixed uniformly by a high-speed mixer, and the mixed materials were put into an extruder for melt blending, and ellipsoidal modified thermoplastic polyurethane elastomer foamed particles were obtained by underwater pelletizing;
[0118] (3) adding 1 kg of the modified thermoplastic polyurethane elastomer foamed particles and 2 kg of water into a 30 L high-pressure foaming reactor, stirring at a speed of 10 r / min, and then injecting high-pressure CO2 through a plunger pump while heating. When the temperature in the reactor reaches 130° C. and the pressure reaches 13 MPa, the pressurization and heating are stopped, and the temperature and pressure are maintained for 80 min to allow the particles to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system;
[0119] (4) opening the discharge valve at the bottom of the autoclave, and releasing the pressure of the polymer-supercritical fluid homogeneous system for foaming at a rate of 35 MPa / min to obtain modified thermoplastic polyurethane elastomer foam beads;
[0120] (5) In a steam molding machine, the water vapor pressure was set to 0.3 MPa, the heating temperature was set to 140° C., and the heating time was set to 40 s, and a sheet was prepared using modified thermoplastic polyurethane elastomer foam beads.
[0121] Comparative Example 1
[0122] Compared with Example 1, unmodified thermoplastic polyurethane elastomer foam beads were prepared:
[0123] Commercially available TPU particles of Ellaston 1185A with a Shore hardness of 40D;
[0124] 1kg of the above TPU particles and 2kg of water were added to a 30L high-pressure foaming kettle, and stirred at a speed of 10r / min. High-pressure CO2 was then injected through a plunger pump and heated at the same time. When the temperature in the kettle reached 125°C and the pressure reached 15MPa, pressurization and heating were stopped. The temperature and pressure were maintained for 60 minutes to make the TPU foamed particles reach a saturated state, and a polymer-supercritical fluid homogeneous system was obtained.
[0125] The discharge valve at the bottom of the autoclave was opened, and the polymer-supercritical fluid homogeneous system was depressurized and foamed at a rate of 30 MPa / min to obtain TPU foamed beads (TPU-F1); the apparent density of TPU-F1 foamed beads was 0.19 g / cm 3 ; Since the melt strength of TPU is not high at high temperature, this causes more cracks inside the foamed beads (such as Figure 4 shown).
[0126] Take 5 foam beads and place them in a laboratory at 25°C and 50% humidity for 72 hours. Observe the appearance of the foam beads and test the apparent density every 24 hours to determine the shrinkage of the foam beads. As shown in Table 1, the shrinkage rate of TPU-F1 foam beads is 15.8% after 24 hours, and the shrinkage rate reaches 31.2% after 48 hours.
[0127] In the steam forming machine, the water vapor pressure is set to 0.20 MPa, the temperature is set to 110 ° C, and the heating time is set to 30 seconds. The TPU-F1 foamed beads can be used to prepare a sheet with a density of 0.31 g / cm 3 , vertical rebound reaches 60%, tensile strength is 2.2MPa, and elongation at break is 288%.
[0128] Comparative Example 2
[0129] Compared with Example 3, unmodified thermoplastic polyurethane elastomer foam beads were prepared:
[0130] Ellaston 1185A TPU with a Shore hardness of 40D was purchased;
[0131] 1kg of the above TPU particles and 2kg of water were added to a 30L high-pressure foaming kettle, and stirred at a speed of 10r / min. High-pressure CO2 was then injected through a plunger pump and heated at the same time. When the temperature in the kettle reached 115°C and the pressure reached 10MPa, pressurization and heating were stopped. The temperature and pressure were maintained for 60 minutes to make the TPU foamed particles reach a saturated state, and a polymer-supercritical fluid homogeneous system was obtained.
[0132] The discharge valve at the bottom of the autoclave was opened, and the polymer-supercritical fluid homogeneous system was depressurized and foamed at a rate of 30 MPa / min to obtain TPU foamed beads (TPU-F2). The apparent density of TPU-F2 foamed beads is 0.19 g / cm 3 .
[0133] Take 5 foam beads and place them in a laboratory at 25°C and 50% humidity for 72 hours. Observe the appearance of the foam beads and test the apparent density every 24 hours to determine the shrinkage of the foam beads (as shown in Table 1). As shown in Table 1, the shrinkage rate of TPU-F1 foam beads is 15.4% after 24 hours, and the shrinkage rate is still 26.9% after 48 hours.
[0134] In the steam forming machine, the water vapor pressure is set to 0.20 MPa, the temperature is set to 110 ° C, and the heating time is set to 30 s. The TPU-F2 foamed beads can be used to prepare a sheet with a density of 0.33 g / cm 3 , vertical rebound reaches 57%, tensile strength is 2.3MPa, and elongation at break is 296%.
[0135] Comparative Example 3
[0136] Compared with Example 1, modified thermoplastic polyurethane elastomer foam beads were prepared using non-2N2(N+1) type LCPAE:
[0137] Ellaston 1185A TPU with a Shore hardness of 40D was purchased commercially, and Pebax 4533 (PA12-based LCPAE) with a Shore hardness of 40D was purchased commercially;
[0138] 70 kg of TPU Ellaston 1185A purchased from BASF, 30 kg of dry Pebax4533 with a hardness of 40D, 0.5 kg of 1098 antioxidant, 0.1 kg of HPN-20E nucleating agent, 0.5 kg of KL-E4370 multifunctional epoxy chain extender, and 0.5 kg of silica were uniformly mixed by a high-speed mixer, and the mixed materials were put into an extruder for melt blending, and ellipsoidal modified thermoplastic polyurethane elastomer foamed particles (UA3) were obtained by underwater pelletizing;
[0139] (3) 1 kg of the modified thermoplastic polyurethane elastomer foamed particles (UA3) and 2 kg of water were added to a 30 L high pressure foaming reactor, and stirring was started at a speed of 10 r / min. High pressure CO2 was then injected through a plunger pump while heating was performed. When the temperature in the reactor reached 125° C. and the pressure reached 15 MPa, pressurization and heating were stopped. The temperature and pressure were maintained for 60 min to allow the particles to reach a saturated state, thereby obtaining a polymer-supercritical fluid homogeneous system.
[0140] (4) opening the discharge valve at the bottom of the autoclave, and releasing the pressure on the polymer-supercritical fluid homogeneous system at a rate of 30 MPa / min to foam the modified thermoplastic polyurethane elastomer foam beads (UA3-F1); the apparent density of the modified thermoplastic polyurethane elastomer foam beads (UA3-F1) is 0.13 g / cm 3 ;
[0141] Take 5 UA3-F1 foam beads and place them in a laboratory at 25°C and 50% humidity for 48 hours. Observe the appearance of the LCPAE foam beads (UA3-F1) and test the apparent density once every 24 hours to determine the shrinkage of the UA3-F1 foam beads (as shown in Table 1). As shown in Table 1, the shrinkage rate of the UA3-F1 foam beads after 24 hours is 23.1%, and the shrinkage rate after 48 hours is still 30.7%.
[0142] (5) In the steam forming machine, the water vapor pressure is set to 0.20 MPa, the temperature is set to 110°C, and the heating time is set to 30 s. The modified thermoplastic polyurethane elastomer foam beads (UA3-F1) can be used to prepare a sheet with a sheet density of 0.17 g / cm 3 , vertical rebound reaches 63%, tensile strength is 1.5MPa, and elongation at break is 221% (as shown in Table 2).
[0143] The present invention examines the shrinkage of the modified thermoplastic polyurethane elastomer foam beads of Examples 1 to 4 and Comparative Examples 1 to 3, as shown in Table 1 below; and the present invention also examines the physical properties of the sheets prepared using Examples 1 to 4 and Comparative Examples 1 to 3, as shown in Table 2 below;
[0144] Table 1: Shrinkage of foamed beads
[0145]
[0146] The only difference between Comparative Example 1 and Example 1 is that unmodified TPU particles are used for direct foaming without modifying the TPU. As can be seen from the above table, the initial density of the modified foamed beads in Example 1 is lower, which means that a higher foaming ratio can be achieved during the foaming process, making the material lighter and more elastic.
[0147] The shrinkage rate of Example 1 (UA1-F1) was 13.3% after 24 hours and remained at 13.3% after 48 hours; while the shrinkage rate of the unmodified TPU foam beads (TPU-F1) reached 15.8% after 24 hours of storage, which was much higher than that of the modified TPU, and the shrinkage rate further increased to 31.2% between 24 hours and 48 hours, showing a significant dimensional change; this indicates that the shrinkage of the unmodified TPU was unstable during storage and the dimensional changes were drastic.
[0148] Furthermore, comparing Comparative Example 2 with Example 3, the only difference is that unmodified TPU particles are used for direct foaming. The shrinkage rate of Example 3 (UA2-F1) is 12.5% after storage for 24 hours, and the shrinkage rate is 18.8% after 48 hours. Although it has increased slightly, it is generally controlled below 20%, showing a relatively stable dimensional change.
[0149] The shrinkage rate of comparative example 2 (TPU-F2) was 15.4% after 24 hours, and the shrinkage rate increased to 26.9% after 48 hours. The foamed beads of unmodified TPU shrank significantly during storage, especially the shrinkage rate increased significantly between 24 hours and 48 hours. This unstable shrinkage behavior indicates that the unmodified TPU has dimensional instability during storage, which has a great impact on the performance and production consistency of the foamed material.
[0150] In the present invention, the modified TPU has a lower shrinkage rate during storage, and the shrinkage change is relatively stable. The dimensional stability of the modified TPU is derived from the higher crystallization temperature and faster crystallization rate of the long carbon chain polyamide (LCPAE) modified material, which enables the foamed beads to maintain a higher structural integrity during storage and avoid significant shrinkage due to the release of internal stress.
[0151] The introduction of LCPAE makes the modified TPU foam beads have good elasticity and shock absorption performance while maintaining lightness. The foamed beads have a more stable structure and a uniform pore wall structure, which reduces the pore collapse caused by shrinkage, making the material have better resilience and durability in actual use.
[0152] In summary, LCPAE modified TPU significantly improves the expansion ratio, dimensional stability and resilience of foam beads, making them suitable for a wider range of applications and overcoming the problems of shrinkage instability and structural instability in the production of unmodified TPU foam materials. The performance of modified TPU foam beads is better during storage and use, especially in situations where high performance and long life are required, and its advantages are more significant.
[0153] The shrinkage rate of Example 1 (UA1-F1) after 24 hours is 13.3%, and it remains at 13.3% after 48 hours, indicating that the size is relatively stable during storage. The shrinkage rate of Comparative Example 1 (TPU-F1) after 24 hours is 15.8%, which rises to 31.2% after 48 hours, showing that the size of the unmodified TPU changes more dramatically during storage and the shrinkage is unstable. The shrinkage rate of Comparative Example 3 (UA3-F1) after 24 hours is 23.1%, which rises to 30.7% after 48 hours, and the shrinkage rate is significantly higher than that of Example 1. This shows that when TPU is modified using a non-2N2 (N+1) type long carbon chain polyamide elastomer (LCPAE), although a higher foaming ratio (i.e., a lower initial density) can be achieved, its dimensional stability is significantly inferior to that after modification using a 2N2 (N+1) type LCPAE.
[0154] Therefore, Example 1 uses 2N2 (N + 1) type LCPAE to modify TPU, so that the foamed beads can maintain a low density after foaming, and the size changes less during storage, the shrinkage rate is stable, and it has high dimensional stability. The initial density of the unmodified TPU is high, and the shrinkage is unstable during storage. The shrinkage rate increases significantly after 48 hours, indicating that the foaming effect of the unmodified TPU is relatively poor and it is difficult to achieve good dimensional stability. The non-2N2 (N + 1) type LCPAE modified TPU has the lowest initial density, indicating that the foaming ratio is high, but the shrinkage rate is significantly higher, and the shrinkage is unstable, and the size changes are large, indicating that the non-2N2 (N + 1) type LCPAE is not ideal in terms of dimensional stability.
[0155] In summary, the technical solution in Example 1 not only achieves a higher foaming ratio by modifying TPU with 2N2(N+1) type LCPAE, but also significantly improves the dimensional stability of the foamed beads during storage, overcoming the problems of unstable shrinkage and drastic dimensional changes in Comparative Examples 1 and 3.
[0156] Table 2: Sheet properties
[0157]
[0158] The density of Example 1 (UA1-F1) and Example 3 (UA2-F1) is 0.16 g / cm 3 and 0.21g / cm 3 , significantly lower than the unmodified comparative example 1 (0.31 g / cm 3 ) and Comparative Example 2 (0.33 g / cm 3 ). Low density means a higher foaming ratio, and there is more air filling inside the material, making the material lighter and thus having excellent elasticity.
[0159] The density of comparative example 3 (UA3-F1) is 0.17 g / cm 3 , although also relatively low, its vertical rebound performance is only 63% compared with that of Example 1, while Example 1 reaches 68%. This shows that simply reducing the density is not enough to effectively improve the elasticity of the material, and the uniformity and stability of the internal structure of the material are equally important.
[0160] The vertical resilience of Examples 1 to 4 is between 65% and 68%, especially Examples 1 and 3 maintain a relatively high resilience (68%), which is complementary to the lower density. The reduction in density makes the material lighter, while the resilience is not weakened, but enhanced due to the improved structural uniformity.
[0161] The vertical rebound of Comparative Example 1 and Comparative Example 2 were 60% and 57% respectively, which were significantly lower than those of the embodiment group. This indicates that the dense material formed by the unmodified TPU after foaming lacks sufficient elastic support. The higher the density, the worse the rebound resilience, making it difficult to cope with applications with high elasticity requirements.
[0162] Low-density materials need to have sufficient ductility while maintaining lightness to ensure that they can deform without breaking under stress. The elongation at break of Example 1 (UA1-F1) and Example 3 (UA2-F1) are 246% and 232% respectively, maintaining good flexibility at a relatively low density.
[0163] The elongation at break of Comparative Example 1 (TPU-F1) and Comparative Example 2 (TPU-F2) are 288% and 296% respectively. Although they seem to have better ductility, their higher density makes the material heavier overall, and their flexibility and elasticity are poor. Therefore, their ductility can only play a role in relatively limited situations and cannot be compared with low-density, high-rebound materials.
[0164] The elongation at break of comparative example 3 (UA3-F1) is 221%, which is significantly lower than that of examples 1 and 3. This shows that, despite its high foaming ratio (low density), its flexibility and ductility are still not as good as those of the 2N2 (N+1) type LCPAE modified ones. This shows that although non-2N2 (N+1) type LCPAE is helpful in improving the density and resilience of TPU, its effect on improving the uniformity and ductility of the internal structure of the material is limited, and it is difficult to achieve the same effect as the 2N2 (N+1) type LCPAE modification.
[0165] In summary, by using 2N2(N+1) type LCPAE to modify TPU, the material achieves an ideal synergistic gain among low density, high rebound and high flexibility. The reduction in density not only reduces the weight of the material, but also improves the elasticity of the material. The higher vertical rebound combined with the elongation at break makes the material exhibit excellent mechanical properties and long-term performance.
[0166] However, whether it is unmodified TPU or TPU modified with non-2N2(N+1) type LCPAE, there is an imbalance between the performances, and it is difficult to achieve the synergistic effect of light weight, high elasticity and flexibility shown in the embodiment group. Therefore, the application of 2N2(N+1) type LCPAE in the present invention significantly improves the comprehensive performance of TPU foaming materials, making it show excellent comprehensive performance in three dimensions of density, elasticity and elongation at break, and is suitable for high-performance and high-demand application scenarios.
[0167] Test Example 1
[0168] This test example verifies the effect of the ratio between thermoplastic polyurethane elastomer (TPU) and long carbon chain polyamide thermoplastic elastomer on product performance:
[0169] On the basis of Example 1, the following test groups were set up. The difference between each test group and Example 1 was only that the ratio of TPU and LCPAE-A was different, as shown in Table 3 below:
[0170] Table 3:
[0171]
[0172]
[0173] As can be seen from the table above, the density of test group 1 increased to 0.16 g / cm2 24 hours after foaming. 3 The shrinkage rate is 14.3%, and the density increases to 0.17g / cm after 48 hours. 3 , the shrinkage rate increased to 21.4%, especially after 48 hours, the shrinkage rate was 21.4%, which was significantly higher than 13.3% in Example 1. This shows that when the TPU content is at the minimum boundary, the dimensional stability of the structure is not as good as that in Example 1, which makes the material prone to large dimensional changes during storage, affecting the overall stability.
[0174] In test group 2, the density increased to 0.20 g / cm2 24 hours after foaming. 3 , the shrinkage rate was 11.1%; after 48 hours, the density further increased to 0.21g / cm 3The shrinkage rate is 16.7%. Compared with Example 1 (the density after 24 hours and 48 hours of foaming is maintained at 0.17g / cm 3 , shrinkage rate is 13.3%), and the density change of test group 2 is more obvious. That is, the increase in density and shrinkage rate of test group 2 after foaming are greater than those of example 1, especially after 48 hours, which shows that when the TPU content is relatively low, the internal pore structure of the material is more likely to collapse and the dimensional stability is poor. Due to the reduction in TPU content, the elongation at break of test group 2 is also significantly lower than that of example 1, indicating that the material has insufficient ductility, relatively weak tensile strength, and poor toughness.
[0175] Compared with Example 1, although the foaming ratio of Test Group 2 has been improved, the overall performance of the material is significantly insufficient, including poor dimensional stability and ductility. Therefore, when the TPU content is low, although a higher foaming ratio may be achieved, the structural stability and flexibility of the material will be significantly reduced, making it difficult for the material to meet high performance requirements in practical applications. In Test Group 3, the density increased to 0.22 g / cm2 24 hours after foaming. 3 , the shrinkage rate was 15.8%; after 48 hours, the density further increased to 0.25g / cm 3 The shrinkage rate is 31.2%. In contrast, the density of Example 1 after 24 hours and 48 hours of foaming is 0.17 g / cm 3 , the shrinkage rate is 13.3%.
[0176] Compared with Example 1, the density of Test Group 3 changed more during storage, especially after 48 hours, the density increased significantly to 0.25 g / cm 3 , and its shrinkage rate is also much higher than that of Example 1, indicating that due to the reduction of LCPAE-A content in the test group 3 material, the crystallization characteristics and dimensional stability of the material are reduced, resulting in easy collapse of the pore structure and large dimensional changes.
[0177] Compared with Example 1, the density and shrinkage of Test Group 4 are higher than those of Example 1, especially the density after 48 hours reaches 0.26 g / cm 3 , the shrinkage rate is as high as 36.8%, which shows that the foaming structure of test group 4 is relatively unstable. The high TPU content leads to a significant decrease in the crystallinity and dimensional stability of the material, and it is difficult to maintain a uniform and stable pore structure, resulting in a denser sheet and easy to shrink. Although the elongation at break is improved by increasing the TPU content, its density is high, the shrinkage rate is significantly increased, the uniformity of the pore structure cannot be effectively maintained, and the overall performance is poor.
[0178] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A method for preparing modified thermoplastic polyurethane elastomer foam beads, characterized in that: The steps include: (1) mixing a thermoplastic polyurethane elastomer, a long carbon chain polyamide thermoplastic elastomer and a processing aid, and then extruding and granulating the mixture to obtain modified thermoplastic polyurethane elastomer foamed particles; (2) placing the modified thermoplastic polyurethane elastomer foamed particles and water into a high-pressure reactor and stirring them, then filling the high-pressure reactor with a supercritical fluid, heating the high-pressure reactor to the softening temperature of the modified thermoplastic polyurethane elastomer foamed particles, so that the modified thermoplastic polyurethane elastomer reaches a saturated state, and obtaining a polymer-supercritical fluid homogeneous system; (3) The polymer-supercritical fluid homogeneous system is depressurized and foamed to obtain modified thermoplastic polyurethane elastomer foam beads.
2. The method for preparing modified thermoplastic polyurethane elastomer foam beads according to claim 1, characterized in that: The thermoplastic polyurethane elastomer is 100 parts by weight, and the long carbon chain polyamide thermoplastic elastomer is 20 to 50 parts by weight; Preferably, the processing aid is selected from one or more of a chain extender, an antioxidant, a nucleating agent or a lubricant; Preferably, the processing aid includes 0.01-2 parts by weight of a chain extender, 0.01-5 parts by weight of an antioxidant, and 0.01-5 parts by weight of a nucleating agent.
3. The method for preparing modified thermoplastic polyurethane elastomer foam beads according to claim 1 or 2, characterized in that: The thermoplastic polyurethane elastomer is polyether polyurethane and / or polyester polyurethane; Preferably, the isocyanate of the thermoplastic polyurethane elastomer is selected from one or more of aliphatic isocyanate, alicyclic isocyanate and aromatic isocyanate; Preferably, the isocyanate of the thermoplastic polyurethane elastomer is selected from one or more of aromatic polyisocyanates and aliphatic polyisocyanates; Preferably, the hardness of the thermoplastic polyurethane elastomer is 30-40D on Shore A; Preferably, the isocyanate of the thermoplastic polyurethane elastomer is selected from one or more of 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 2,2'-diphenylmethane diisocyanate (2,2'-MDI), xylylene diisocyanate (XDI), 1,5-naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), 1,4-cyclohexyl diisocyanate (CHDI), hexamethylene diisocyanate (HDI), decane-1,10-diisocyanate and dicyclohexylmethane-4,4'-diisocyanate (H12MDI); Preferably, the isocyanate of the thermoplastic polyurethane elastomer is 4,4'-diphenylmethane diisocyanate (4,4'-MDI).
4. A method for preparing modified thermoplastic polyurethane elastomer foam beads according to any one of claims 1 to 3, characterized in that: The polyol of the thermoplastic polyurethane elastomer is selected from one or more of polyester polyol, polylactone polyol, polycarbonate polyol and polyether polyol; Preferably, the polyol of the thermoplastic polyurethane elastomer is a polyether polyol.
5. A method for preparing modified thermoplastic polyurethane elastomer foam beads according to any one of claims 1 to 4, characterized in that: The chain extender of the thermoplastic polyurethane elastomer is selected from one or more diols having 2 to 10 carbon atoms; Preferably, the chain extender of the thermoplastic polyurethane elastomer is selected from one or more of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,3-butanediol, 1,5-pentanediol, 1,4-cyclohexanediol, hydroquinone di(hydroxyethyl) ether and neopentyl glycol; Preferably, the chain extender of the thermoplastic polyurethane elastomer is 1,4-butanediol.
6. A method for preparing modified thermoplastic polyurethane elastomer foam beads according to any one of claims 1 to 5, characterized in that: The long carbon chain polyamide thermoplastic elastomer is formed by polycondensation of a polyamide hard segment and a polyether soft segment in which the carbon number of the diamine and the carbon number of the dibasic acid are 2N2(N+1); Preferably, the polyamide hard segment and the polyether soft segment are connected by an ester bond or an amide bond; Preferably, the polyamide hard segment is selected from one or more of polyamide 1416, polyamide 1214, polyamide 1012 or polyamide 810; Preferably, the polyamide hard segment is selected from polyamide 1214 and polyamide 1012; Preferably, the polyamide hard segment is polyamide 1012; Preferably, the polyether soft segment is selected from one or more of polyoxyethylene ether, polyoxypropylene ether, and polytetramethylene oxide ether; Preferably, the polyether soft segment is polytetramethylene oxide.
7. A method for preparing modified thermoplastic polyurethane elastomer foam beads according to any one of claims 1 to 6, characterized in that: In the step (2), the supercritical fluid includes supercritical CO2 and / or supercritical N2, the supercritical fluid is filled to reach 10-25MPa, the autoclave is heated to 90-160°C, and maintained for 30-120min; Preferably, in step (2), supercritical fluid is charged to reach 12-15 MPa, and the high-pressure reactor is heated to 110-130° C. and maintained for 60-90 minutes.
8. A method for preparing modified thermoplastic polyurethane elastomer foam beads according to any one of claims 1 to 7, characterized in that: In the step (3), a rapid pressure relief method is used for pressure relief, and the pressure relief rate is 10-60 MPa / min; Preferably, the pressure relief rate is 30-40 MPa / min.
9. A modified thermoplastic polyurethane elastomer foamed bead, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8, the density is 0.1-0.3g / cm 3 The cell diameter of the foamed beads is 10-100 μm, and the cell density is 2×10 7 -2×10 9 Pieces / cm 3 .
10. Use of the modified thermoplastic polyurethane elastomer foam beads according to any one of claims 1 to 9 in the preparation of foamed materials, characterized in that: The modified thermoplastic polyurethane elastomer foam beads are placed in the mold cavity of a molding machine, steam is introduced and heated at a pressure of 0.1-0.4 MPa until the foam beads expand, extrude and adhere to each other, and after cooling and demolding, a density of 0.15-0.35 g / cm is formed. 3 Foaming material; Preferably, the heating temperature is 100-150°C and the heating time is 10-120s; Preferably, the pressure of the water vapor introduced is 0.2-0.3 MPa, the heating temperature is 110-130° C., and the heating time is 20-40 s.
Citation Information
Patent Citations
Thermoplastic polyurethane elastomer foamed beads and preparation method thereof
CN104130439A
Extruded and foamed thermoplastic polyurethane elastomer particle and preparation method thereof
CN108239386A
Pebax / TPU (Thermoplastic Polyurethane) blended foaming material
CN108250734A
Low-shrinkage long-carbon-chain polyamide elastomer foamed bead as well as preparation method and application thereof
CN114316345A
Cited By
Preparation method of thermoplastic polyester elastomer foam material
CN121468998A